New records of the genus Miconchus (Mononchida, Anatonchidae) for Vietnam nematode fauna - Tam, Vu Thi Thanh (Academia Journal of Biology, 2020)
Two species of the genus Miconchus, viz. M. dahousiensis and M. baeticus, were recorded for the first time in Vietnam. The two collected species from Tuyen Quang, Ha Giang and Bac Can Provinces were redescribed and illustrated.